Indonesian Business Culture and Sharia Compliance: Does Better Pre or Post Merger Policy? - Isman, Ainul Fatha; Rodhoni, Ahmad; Hidayah, Nur; Umar, Muhammad; Ibrashen, Ahmed Amhamed Ahmed (Graduate School of UIN Syarif Hidayatullah Jakarta, 2024)
Sharia compliance is an important entity of Islamic banks that needs to be maintained. The Indonesian merger policy can be a benchmark for how much Islamic banking pays attention to the dimensions of Sharia compliance. This study analyses the comparison of Sharia compliance pre-post merger policy of Islamic banks in Indonesia. This quantitative study uses a statistical approach to different tests, namely the nonparametric Wilcoxon Signed Rank Test. Data is collected from Islamic banking financial reports pre-merger (2019-2020) and post-merger (2021-2022). The research findings show differences in the Sharia compliance culture in Islamic banks pre-post merger. The Sharia compliance ratio of Islamic banking is better post-merger. This is because the merger makes the Sharia ecosystem more positive, increases religiosity values, and consistently applies existing Sharia standards. The study results have implications for the development of merger studies in Islamic banking, and the implementation of Sharia compliance needs to be continuously improved as a basic barometer of Islamic banking entities in Indonesia. The research limitations are expected to examine the culture of sharia compliance within the framework of strategic policies that need to be implemented by sharia banks.